2016
DOI: 10.1038/srep37593
|View full text |Cite
|
Sign up to set email alerts
|

Lower Vitamin D Metabolites Levels Were Associated With Increased Coronary Artery Diseases in Type 2 Diabetes Patients in India

Abstract: The purpose of the present study was to measure six vitamin D metabolites and to find the association between vitamin D deficiency and coronary artery diseases in diabetes (T2DM_CAD). Four groups [control (n = 50), type 2 diabetes (T2DM, n = 71), coronary artery diseases (CAD, n = 28), T2DM_CAD (n = 38)] of total 187 subjects were included in the study. Six vitamin D metabolites (D2, D3, 25(OH)D2, 25(OH)D3, 1,25(OH)2D2, 1,25(OH)2D3), total 25(OH)D and total 1,25(OH)2D were measured by UPLC/APCI/HRMS method in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…[ 9 ] 25-Hydroxyvitamin D3 (25OHD3) can be obtained from various sources: the exposure of the epidermis to the sunlight allows the body to synthesize 25OHD3, we can take additional supplements of fish oil which contains high levels of 25OHD3. [ 10 ] It has been found that lower serum 25OHD3 levels are epidemiologically related to higher occurrence of respiratory infections both in upper and lower respiratory tracts, and vitamin D deficiency is closely connected with badly aggravation of asthma. [ 11 ] It has been demonstrated that 25OHD3 supplementation helps more to elevate quality of life (QOL) effectively than to alleviate the pulmonary damages caused by severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] 25-Hydroxyvitamin D3 (25OHD3) can be obtained from various sources: the exposure of the epidermis to the sunlight allows the body to synthesize 25OHD3, we can take additional supplements of fish oil which contains high levels of 25OHD3. [ 10 ] It has been found that lower serum 25OHD3 levels are epidemiologically related to higher occurrence of respiratory infections both in upper and lower respiratory tracts, and vitamin D deficiency is closely connected with badly aggravation of asthma. [ 11 ] It has been demonstrated that 25OHD3 supplementation helps more to elevate quality of life (QOL) effectively than to alleviate the pulmonary damages caused by severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been gaining attention for non-classical roles such as regulation of inflammation, immunity, cell cycle and metabolism. Association between vitamin D deficiency and adverse cardiometabolic outcomes has been repeatedly shown in patients, but the therapeutic role of vitamin D supplementation remains controversial [3]. Clinical studies have yielded conflicting results regarding the potential benefits of vitamin D in subjects with cardiometabolic diseases [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier shown vitamin D deficiency is associated with increased prevalence of type 2 diabetes with and without coexisting coronary artery disease, both important risk factors for heart failure (3). Conditions such as chronic renal failure precipitate vitamin D deficiency as well as cardiac failure (4).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays an essential function in the bone and mineral metabolism. Vitamin D deficiency is a frequent global health dilemma and is the reason for causing osteoporosis and osteomalacia, rickets, and other bone-related disorders [13]. In the most recent decade, researchers perceived that decreased serum 25-hydroxy vitamin D levels were related to metabolic diseases like type 1 diabetes, obesity, insulin resistance, cardiovascular diseases, and cancer [14][15][16].…”
Section: Introductionmentioning
confidence: 99%